A dendrite free Zn‐Fe hybrid redox flow battery for renewable energy storage. Issue 1 (18th August 2021) - Jeena, C. Balakrishnan; Elsa, P. Jose; Moly, P. Peter; Ambily, K. Jacob; Joy, Vadakkan T.
Abstract: About two thirds of global greenhouse emissions is caused by burning of fossil fuels for energy purposes and this has spurred great research interest to develop renewable energy technologies based on wind, solar power, and so on. Redox flow batteries (RFB) are receiving wide attention as scalable energy‐storage systems to address the intermittency issues of renewable energy sources. However, for widespread commercialization, the redox flow batteries should be economically viable and environmentally friendly. Zinc based batteries are good choice for energy storage devices because zinc is earth abundant and zinc metal has a moderate specific capacity of 820 mA hg −1 and high volumetric capacity of 5851 mA h cm −3 . We herein report a zinc‐iron (Zn‐Fe) hybrid RFB employing Zn/Zn(II) and Fe(II)/Fe(III) redox couples as positive and negative redox systems, respectively, separated by a self‐made anion exchange membrane (AEM). The battery delivers a good discharge voltage of approximately 1.34 V at 25 mA cm −2, with a coulombic efficiency (CE) of 92%, voltage efficiency (VE) of 85% and energy efficiency (EE) of 78% for 30 charge‐discharge cycles. Repeated galvanostatic charge/discharge cycles show no degradation in performance, confirming the excellent stability of the system. A key advancement in the present Zn‐Fe hybrid redox flow battery with AEM separator is that no dendrite growth was observed on zinc electrode on repeated charge‐discharge cycles, which was the serious drawback of many previously reported zinc based redox flow batteries.